A graphite film and a method for manufacturing the same
Patent Information
- Application Number
- CN202611148012.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]本发明所要解决的技术问题是提供一种石墨薄膜及其制备方法,旨在解决石墨薄膜在碳化过程中收缩率过大的问题
一方面,由于采用了将树脂材料在惰性氛围中进行烧制形成沥青状物质,并进一步球磨得到沥青粉末的技术手段,通过惰性条件下的预热解处理,使树脂中的部分非碳元素提前脱除,并促进分子链断裂、芳构化及碳骨架重组,提高沥青前驱体的芳香结构含量和残碳率,解决了现有树脂薄膜直接碳化过程中因氢、氧等非碳元素大量逸出导致碳骨架损失严重、体积收缩率过大的问题,从而达到了提高碳化过程中降低石墨薄膜体积收缩率技术效果。
Smart Images

Figure CN122916124A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of graphene materials, specifically to a graphite film and its preparation method. Background Technology
[0002] Graphene is a type of carbon atom arranged in sp... 2 Two-dimensional honeycomb carbon materials formed by hybrid connections possess excellent in-plane thermal conductivity, electrical conductivity, mechanical properties, and chemical stability. Based on the efficient heat transfer characteristics of graphene's layered structure, graphite film materials with graphene layered structure features can be prepared by curing, pyrolytic carbonization, and high-temperature graphitization of resin precursors such as phenolic resin, polyimide resin, and furfuryl alcohol resin. Through dehydrogenation, deoxygenation, aromatization, and carbon layer rearrangement processes in the resin precursors, graphite films can be obtained, endowing them with excellent in-plane thermal conductivity, a low coefficient of thermal expansion, and good chemical stability. Therefore, graphite film materials based on graphene's structural characteristics are widely used in heat dissipation of electronic devices, thermal management of power batteries, flexible electronic devices, and heat diffusion of high-power devices. They can effectively promote rapid heat transfer along the film surface, reduce local heat accumulation, and improve the operational stability of equipment.
[0003] However, during the carbonization process of graphite film preparation, the resin molecular chain contains a large number of non-carbon elements such as hydrogen and oxygen, which will escape in the form of small molecules such as water, carbon monoxide, and carbon dioxide under high temperature conditions. At the same time, the carbon skeleton breaks, aromatizes, and rearranges, causing the precursor film to undergo significant volume shrinkage. In addition, since the graphite film precursor film usually has a small thickness (generally tens to hundreds of micrometers), its structure cannot effectively compensate for the large shrinkage changes during the carbonization process, resulting in an excessive overall shrinkage rate of the film. This easily leads to defects such as dimensional deviations, warping, curling, and even cracking, which seriously affects the structural integrity and thermal conductivity of the graphite film and makes it difficult to improve the yield of graphite film preparation. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to provide a graphite film and a method for preparing the same, which aims to solve the problem of excessive shrinkage rate of graphite film during carbonization.
[0005] To address the aforementioned technical problems, a method for preparing graphite thin films is proposed, comprising the following steps: S1. The resin material is fired in an inert atmosphere to obtain an asphalt-like substance, and then the asphalt-like substance is ball-milled to obtain asphalt powder. S2. The asphalt powder is divided into two batches and dissolved and filtered in an organic solvent to obtain a first asphalt solution and a second asphalt solution. The first asphalt solution is sprayed onto the surface of the mold and cured to obtain a bottom film. The second asphalt solution is then sprayed onto the surface of the bottom film and cured to obtain an asphalt film. The mass concentration of asphalt powder in the first asphalt solution is higher than that in the second asphalt solution. S3. Place the asphalt film on a graphite plate and flatten it with a breathable pressing block to carbonize it, thereby obtaining a glassy carbon film. Then, graphitize the glassy carbon film to obtain a graphite film.
[0006] In addition, a graphite film is provided, which is prepared by the above-described method for preparing a graphite film.
[0007] As can be seen from the above technical solutions, the exemplary embodiments disclosed herein possess at least the following advantages and positive effects: On the one hand, by employing a technique of firing resin materials in an inert atmosphere to form asphalt-like substances and then ball milling them to obtain asphalt powder, and through preheating and decomposition under inert conditions, some non-carbon elements in the resin are removed in advance, and molecular chain breakage, aromatization, and carbon skeleton recombination are promoted. This increases the aromatic structure content and residual carbon rate of the asphalt precursor, solving the problem of severe carbon skeleton loss and excessive volume shrinkage caused by the large escape of non-carbon elements such as hydrogen and oxygen during the direct carbonization process of existing resin films. Thus, the technical effect of improving the reduction of graphite film volume shrinkage during carbonization is achieved.
[0008] On the other hand, by setting the first asphalt solution as a high-concentration asphalt solution to form the lower layer structure and the second asphalt solution as a low-concentration asphalt solution to form the upper layer structure, during the carbonization process, the intermolecular constraint of asphalt molecules in the low-concentration asphalt region is weak. Under the pressure provided by the air-permeable block, the aromatic carbon components with high migration activity migrate to the high-concentration asphalt region and further condense under high temperature conditions to form a carbon structure. This compensates for the structural voids caused by the carbonization shrinkage in the high-concentration region, solves the problem of structural defects caused by the rapid shrinkage of the carbon skeleton during the carbonization process of the high-concentration asphalt layer, and thus achieves the effect of reducing the overall volume shrinkage rate of the graphite film. Attached Figure Description
[0009] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this disclosure and, together with the description, serve to explain the principles of this disclosure. It is obvious that the drawings described below are merely some embodiments of this disclosure, and those skilled in the art can obtain other drawings based on these drawings without any inventive effort. In the drawings: Figure 1This is a schematic diagram of a method for preparing a graphite film in one embodiment; Figure 2 This is a schematic diagram of step S1 in a method for preparing a graphite film in one embodiment; Figure 3 This is a schematic diagram of step S2 in the method for preparing a graphite film in one embodiment; Figure 4 This is a schematic diagram of step S3 in the method for preparing a graphite film in one embodiment. Detailed Implementation
[0010] Exemplary embodiments will now be described more fully with reference to the accompanying drawings. However, these exemplary embodiments can be implemented in many forms and should not be construed as limited to the examples set forth herein; rather, these embodiments are provided so that this disclosure will be more thorough and complete, and will fully convey the concept of the exemplary embodiments to those skilled in the art.
[0011] Furthermore, the described features or characteristics may be combined in any suitable manner in one or more embodiments. Numerous specific details are provided in the following description to give a thorough understanding of embodiments of this disclosure. However, those skilled in the art will recognize that the technical solutions of this disclosure may be practiced without one or more of the specific details, or other methods, steps, etc. may be employed. In other instances, well-known methods, implementations, or operations are not shown or described in detail to avoid obscuring various aspects of this disclosure.
[0012] The flowcharts shown in the accompanying drawings are merely illustrative and do not necessarily include all content and operations / steps, nor do they necessarily have to be performed in the described order. For example, some operations / steps can be broken down, while others can be combined or partially combined; therefore, the actual execution order may change depending on the specific circumstances.
[0013] Please refer to Figure 1 This invention proposes a method for preparing graphite thin films, the method comprising the following steps: S1. The resin material is fired in an inert atmosphere to obtain an asphalt-like substance, and then the asphalt-like substance is ball-milled to obtain asphalt powder.
[0014] The resin material in step S1 includes at least one of phenolic resin, furan resin, polycarbodiimide resin, and polyimide resin.
[0015] By using at least one of phenolic resin, furan resin, polycarbodiimide resin, and polyimide resin as a carbonization precursor and pre-firing it in an inert atmosphere to obtain an asphalt-like substance, the resin material undergoes dehydrogenation, deoxygenation, denitrification, and molecular chain rearrangement reactions before entering the film forming and subsequent carbonization processes. This promotes the transformation of the resin structure into a high-aromatic, high-carbon asphalt structure, increases the effective carbon content and residual carbon rate in the precursor, and reduces the mass loss caused by the escape of non-carbon elements during the subsequent high-temperature carbonization process. At the same time, ball milling the asphalt-like substance into powder can improve the dispersion uniformity of the precursor, enabling it to form a more uniform carbon source distribution during the subsequent dissolution and film formation process.
[0016] Step S1 includes: S1.1. The resin material is fired in an inert atmosphere at 370~550℃ for 0.5~2h to obtain an asphalt-like substance.
[0017] By pre-firing the resin material in an inert atmosphere at 370-550℃, the resin molecular chains undergo thermal decomposition, dehydrogenation, deoxygenation, and aromatization reactions under oxygen-deficient conditions, gradually transforming the resin, which originally had a high molecular chain structure, into an asphalt-like substance rich in aromatic structures. In this process, the inert atmosphere prevents the resin material from oxidizing and burning, reducing carbon loss and preserving the aromatic carbon structures formed during pyrolysis. Simultaneously, the suitable firing temperature promotes the breaking of resin molecular chains and the rearrangement of carbon structures, resulting in an asphalt-like substance with a high carbon content and good thermal stability.
[0018] S1.2 Add the asphalt-like substance to a ball mill and use grinding balls to ball mill it to obtain asphalt powder with a particle size of 20~50μm. The grinding balls are polyurethane-coated iron core grinding balls with a particle size of 3~10mm.
[0019] By adding asphalt-like substances into a ball mill and mechanically grinding them using polyurethane-coated iron-core grinding balls, the lumpy asphalt-like substances are broken down by impact, compression, and shearing, forming uniform asphalt powder with a particle size of 20-50 μm. The polyurethane coating reduces rigid collisions between the grinding balls and the asphalt material during grinding, preventing structural damage due to localized overheating or severe impact. Simultaneously, the iron core structure provides sufficient grinding strength, improving crushing efficiency and resulting in a stable particle size distribution for the asphalt particles. By controlling the asphalt powder particle size, the contact area during subsequent dissolution can be increased, promoting uniform dissolution of asphalt components in the organic solvent, reducing the formation of large undissolved particles, and resulting in an asphalt solution with good homogeneity and fluidity.
[0020] S2. The asphalt powder is divided into two batches and dissolved and filtered in an organic solvent to obtain a first asphalt solution and a second asphalt solution. The first asphalt solution is sprayed onto the surface of the mold and cured to obtain a bottom film. Then the second asphalt solution is sprayed onto the surface of the bottom film and cured to obtain an asphalt film. The mass concentration of asphalt powder in the first asphalt solution is higher than that in the second asphalt solution.
[0021] The organic solvent in step S2 includes at least one of polyvinyl chloride, petroleum ether, methyl chloride, and xylene.
[0022] By dividing asphalt powder into two batches and preparing first and second asphalt solutions of different concentrations, respectively, and then using a layered spraying method to form an asphalt film with a concentration gradient, different carbon content regions are formed within the film. During the subsequent carbonization process, the asphalt components in the low-concentration regions have higher flow and migration capabilities, and under the action of heat and interlayer pressure, they can migrate to the high-concentration regions and further condense to form carbon structures. This compensates for the loss of carbon skeleton caused by the removal of non-carbon elements during the carbonization process in the high-concentration regions. At the same time, the high-concentration regions can provide a higher carbon source, improve the residual carbon rate of the overall precursor, and increase the carbon retention per unit volume during the carbonization process.
[0023] Step S2 includes: S2.1. Add the asphalt powder in two batches to an organic solvent and stir for 60-120 minutes at 50-80℃ and 300-500rpm to obtain a first asphalt solution and a second asphalt solution. The concentration of asphalt powder in the first asphalt solution is 320-410g / L, and the concentration of asphalt powder in the second asphalt solution is 200-300g / L.
[0024] By adding asphalt powder in two batches to an organic solvent and stirring at 50–80°C and 300–500 rpm, the asphalt particles are fully wetted, swollen, and gradually dissolved in the solvent, forming a first and second asphalt solution with uniform component distribution. Controlling the stirring temperature reduces intermolecular forces in asphalt, promotes the diffusion of aromatic components into the solvent, and improves asphalt dissolution efficiency; controlling the stirring speed enhances mass transfer between the solvent and asphalt particles, reduces particle agglomeration, and improves solution homogeneity. By setting a higher asphalt powder concentration in the first asphalt solution and a lower concentration in the second asphalt solution, a carbon source concentration gradient structure is created in the subsequently formed asphalt film, providing a basis for carbon component migration and shrinkage compensation between different regions during carbonization.
[0025] In one embodiment, step S2.1 further includes: S2.1 Divide the asphalt powder into two batches. Add the first batch of asphalt powder and carbon nanofibers with a length of 1~5μm to an organic solvent and stir for 60~120min at 50~80℃ and 300~500rpm to obtain the first asphalt solution. Add the second batch of asphalt powder to an organic solvent and stir for 60~120min at 50~80℃ and 300~500rpm to obtain the second asphalt solution. The concentration of asphalt powder in the first asphalt solution is 320~410g / L and the concentration of carbon nanofibers is 5~15g / L. The concentration of asphalt powder in the second asphalt solution is 200~300g / L.
[0026] By adding carbon nanofibers of a certain concentration and length range to the first asphalt solution, the carbon nanofibers can be uniformly dispersed in the high-concentration asphalt layer. In the subsequent carbonization process, the carbon nanofibers themselves have high thermal stability and carbon retention rate, and can serve as a stable carbon skeleton structure, reducing the collapse of the carbon structure caused by the escape of non-carbon elements during asphalt pyrolysis.
[0027] S2.2 Spray the first asphalt solution onto the surface of the mold to form a first film. Then, in an inert atmosphere, heat the first film to 300-400°C at a rate of 1-3°C / min and keep it at that temperature for 40-100 minutes to cure it, thus obtaining the bottom film.
[0028] S2.3. Spray the second asphalt solution onto the surface of the base film to form the second film. Then, in an inert atmosphere, heat the second film to 300-400℃ at a rate of 1-3℃ / min and keep it at that temperature for 30-60 minutes to cure it, thus obtaining the asphalt film.
[0029] By sequentially spraying a first asphalt solution and a second asphalt solution to form a film, and then curing it at 300-400℃ in an inert atmosphere, the organic solvent in the asphalt solution gradually evaporates, promoting further cross-linking and structural stabilization of the asphalt molecular chains, thus improving the degree of curing of the asphalt film. At the same time, using a slow heating rate of 1-3℃ / min for curing can reduce the internal stress caused by rapid solvent escape and temperature changes, avoiding problems such as cracking and deformation of the film, and giving the resulting asphalt film good smoothness, density and structural stability.
[0030] The total thickness of the first film and the second film is 100~300μm, and the thickness ratio of the first film to the second film is (65~75):(25~35).
[0031] By controlling the thickness ratio of the first film to the second film to be (65~75):(25~35), a reasonable carbon source gradient distribution structure is formed inside the asphalt film. The first film, representing the high-concentration asphalt region, occupies a larger film thickness, providing sufficient carbon source reserves, while the second film, representing the low-concentration region, maintains an appropriate thickness to compensate for carbon component migration. By limiting the thickness ratio of the two films, a balance can be achieved between the high-concentration and low-concentration regions, avoiding insufficient carbon source due to an excessively thin first film and uneven overall carbon source distribution due to an excessively thick second film, thus ensuring the structural stability of the asphalt film.
[0032] S3. Place the asphalt film on a graphite plate and flatten it with a breathable pressing block to carbonize it, thereby obtaining a glassy carbon film. Then, graphitize the glassy carbon film to obtain a graphite film.
[0033] In step S3, the porosity of the air-permeable block is >80%, and the weight of the air-permeable block on the asphalt film is less than 0.1 g / cm³. 2 .
[0034] The graphite films obtained through the above carbonization and graphitization processes, due to the external pressure provided by the permeable pressure block during formation, maintain close contact between different concentration regions within the asphalt film. This promotes the migration of highly mobile aromatic carbon components from low-concentration asphalt regions to high-concentration asphalt regions. During high-temperature carbonization, further aromatization, condensation, and carbon network reorganization occur, filling the structural voids in high-concentration asphalt regions caused by the removal of non-carbon elements and the shrinkage of the carbon skeleton, thus improving the continuity and density of the carbon structure. Simultaneously, after graphitization, the compensated carbon structure further transforms into a continuous and ordered graphite layer structure, reducing internal shrinkage defects in the graphite film and minimizing volume shrinkage and dimensional changes caused by localized carbon loss. Step S3 includes: S3.1 Place the asphalt film on a graphite plate and flatten it with a breathable pressing block. Then, in an inert atmosphere, heat it to 1000℃ at a rate of 2~7℃ / min for 3~6 hours to obtain a glassy carbon film.
[0035] By placing an asphalt film on a graphite plate and flattening it with a permeable pressing block, and then heating it to 1000℃ in an inert atmosphere for carbonization, non-carbon elements in the asphalt film are gradually removed, and carbon structure rearrangement is promoted to form a stable glassy carbon film. Simultaneously, the permeable pressing block provides appropriate constraint on the film, reducing warping and deformation during carbonization, and the permeable structure facilitates the escape of volatile gases, preventing internal defects. By controlling the heating rate and holding time, the carbonization process is made more uniform, resulting in a glassy carbon film with a complete structure and a smooth surface.
[0036] S3.2. Heat the glassy carbon film to 2800-3000℃ at a rate of 90-110℃ / h, hold for 3-5 hours, and then cool down to obtain a graphite film.
[0037] By graphitizing glassy carbon thin films at high temperatures of 2800–3000℃, the disordered carbon structure within the glassy carbon undergoes further rearrangement and crystallization, promoting the formation of a regularly arranged graphite layered structure and increasing the degree of graphitization. Simultaneously, controlling the heating rate and holding time ensures a more complete carbon structure transformation process, reducing thermal stress concentration caused by rapid temperature increases and guaranteeing uniform graphite layer formation. After graphitization, the resulting graphite thin film exhibits a more continuous and dense carbon layer structure, improving its structural stability and integrity, thus yielding a graphite thin film with stable performance.
[0038] In addition, a graphite film is provided, which is prepared by the above-described method for preparing a graphite film.
[0039] For example, the present invention provides the following specific embodiments to illustrate the specific preparation method: Example 1: S1.1 Phenolic resin is calcined at 450°C for 1.2 hours in an inert atmosphere to obtain an asphalt-like substance; S1.2 Add the asphalt-like substance to a ball mill and use grinding balls to ball mill it to obtain asphalt powder with a particle size of 35μm. The grinding balls are polyurethane-coated iron core grinding balls with a particle size of 6mm. S2.1. Add the asphalt powder in two batches to xylene and stir for 90 minutes at 65℃ and 400 rpm to obtain a first asphalt solution and a second asphalt solution. The concentration of asphalt powder in the first asphalt solution is 370 g / L and the concentration of asphalt powder in the second asphalt solution is 250 g / L. S2.2 Spray the first asphalt solution onto the surface of the mold to form a first film with a thickness of 140μm. Then, in an inert atmosphere, heat the first film to 350℃ at a rate of 2℃ / min and keep it at that temperature for 70min to cure it, thus obtaining the bottom film. S2.3. Spray the second asphalt solution onto the surface of the base film to form a second film with a thickness of 60 μm. Then, in an inert atmosphere, heat the second film to 350°C at a rate of 2°C / min and keep it at that temperature for 45 min to cure it, thus obtaining the asphalt film. S3.1 Place the asphalt film on a graphite plate and flatten it with a breathable pressing block with a porosity > 80%. Then, in an inert atmosphere, heat it to 1000℃ at 5℃ / min and carbonize it for 4.5h to obtain a glassy carbon film. S3.2. The glassy carbon film is heated to 2900℃ at a rate of 100℃ / h, held at that temperature for 4h, and then cooled to obtain a graphite film.
[0040] Example 2: S1.1 Phenolic resin is calcined at 450°C for 1.2 hours in an inert atmosphere to obtain an asphalt-like substance; S1.2 Add the asphalt-like substance to a ball mill and use grinding balls to ball mill it to obtain asphalt powder with a particle size of 35μm. The grinding balls are polyurethane-coated iron core grinding balls with a particle size of 6mm. S2.1. Divide the asphalt powder into two batches. Add the first batch of asphalt powder and carbon nanofibers with a length of 3μm to xylene and stir at 65℃ and 400rpm for 90min to obtain the first asphalt solution. Add the second batch of asphalt powder to xylene and stir at 65℃ and 400rpm for 90min to obtain the second asphalt solution. The concentration of asphalt powder in the first asphalt solution is 370g / L and the concentration of carbon nanofibers is 10g / L. The concentration of asphalt powder in the second asphalt solution is 250g / L. S2.2 Spray the first asphalt solution onto the surface of the mold to form a first film with a thickness of 140μm. Then, in an inert atmosphere, heat the first film to 350℃ at a rate of 2℃ / min and keep it at that temperature for 70min to cure it, thus obtaining the bottom film. S2.3. Spray the second asphalt solution onto the surface of the base film to form a second film with a thickness of 60 μm. Then, in an inert atmosphere, heat the second film to 350°C at a rate of 2°C / min and keep it at that temperature for 45 min to cure it, thus obtaining the asphalt film. S3.1 Place the asphalt film on a graphite plate and flatten it with a breathable pressing block with a porosity > 80%. Then, in an inert atmosphere, heat it to 1000℃ at 5℃ / min and carbonize it for 4.5h to obtain a glassy carbon film. S3.2. The glassy carbon film is heated to 2900℃ at a rate of 100℃ / h, held at that temperature for 4h, and then cooled to obtain a graphite film.
[0041] The process is basically the same as in Example 1, except that the first asphalt solution in step S2.1 also contains carbon nanofibers with a concentration of 10 g / L and a length of 3 μm.
[0042] Example 3: S1.1 Phenolic resin is calcined at 450°C for 1.2 hours in an inert atmosphere to obtain an asphalt-like substance; S1.2 Add the asphalt-like substance to a ball mill and use grinding balls to ball mill it to obtain asphalt powder with a particle size of 35μm. The grinding balls are polyurethane-coated iron core grinding balls with a particle size of 6mm. S2.1. Add the asphalt powder in two batches to xylene and stir for 90 minutes at 65℃ and 400 rpm to obtain a first asphalt solution and a second asphalt solution. The concentration of asphalt powder in the first asphalt solution is 370 g / L and the concentration of asphalt powder in the second asphalt solution is 250 g / L. S2.2 Spray the first asphalt solution onto the surface of the mold to form a first film with a thickness of 130μm. Then, in an inert atmosphere, heat the first film to 350℃ at a rate of 2℃ / min and keep it at that temperature for 70min to cure it, thus obtaining the bottom film. S2.3. Spray the second asphalt solution onto the surface of the base film to form a second film with a thickness of 70 μm. Then, in an inert atmosphere, heat the second film to 350°C at a rate of 2°C / min and keep it at that temperature for 45 min to cure it, thus obtaining the asphalt film. S3.1 Place the asphalt film on a graphite plate and flatten it with a breathable pressing block with a porosity > 80%. Then, in an inert atmosphere, heat it to 1000℃ at 5℃ / min and carbonize it for 4.5h to obtain a glassy carbon film. S3.2. The glassy carbon film is heated to 2900℃ at a rate of 100℃ / h, held at that temperature for 4h, and then cooled to obtain a graphite film.
[0043] The process is basically the same as in Example 1, except that the thickness of the first film in step S2.2 is 130 μm and the thickness of the second film in step S2.3 is 70 μm.
[0044] Example 4: S1.1 Phenolic resin is calcined at 450°C for 1.2 hours in an inert atmosphere to obtain an asphalt-like substance; S1.2 Add the asphalt-like substance to a ball mill and use grinding balls to ball mill it to obtain asphalt powder with a particle size of 35μm. The grinding balls are polyurethane-coated iron core grinding balls with a particle size of 6mm. S2.1. Add the asphalt powder in two batches to xylene and stir for 90 minutes at 65℃ and 400 rpm to obtain a first asphalt solution and a second asphalt solution. The concentration of asphalt powder in the first asphalt solution is 370 g / L and the concentration of asphalt powder in the second asphalt solution is 250 g / L. S2.2 Spray the first asphalt solution onto the surface of the mold to form a first film with a thickness of 150μm. Then, in an inert atmosphere, heat the first film to 350℃ at a rate of 2℃ / min and keep it at that temperature for 70min to cure it, thus obtaining the bottom film. S2.3. Spray the second asphalt solution onto the surface of the base film to form a second film with a thickness of 50 μm. Then, in an inert atmosphere, heat the second film to 350°C at a rate of 2°C / min and keep it at that temperature for 45 min to cure it, thus obtaining the asphalt film. S3.1 Place the asphalt film on a graphite plate and flatten it with a breathable pressing block with a porosity > 80%. Then, in an inert atmosphere, heat it to 1000℃ at 5℃ / min and carbonize it for 4.5h to obtain a glassy carbon film. S3.2. The glassy carbon film is heated to 2900℃ at a rate of 100℃ / h, held at that temperature for 4h, and then cooled to obtain a graphite film.
[0045] The process is basically the same as in Example 1, except that the thickness of the first film in step S2.2 is 150 μm and the thickness of the second film in step S2.3 is 50 μm.
[0046] Comparative Example 1: S1.1 Phenolic resin is calcined at 450°C for 1.2 hours in an inert atmosphere to obtain an asphalt-like substance; S1.2 Add the asphalt-like substance to a ball mill and use grinding balls to ball mill it to obtain asphalt powder with a particle size of 35μm. The grinding balls are polyurethane-coated iron core grinding balls with a particle size of 6mm. S2.1. Add the asphalt powder in two batches to xylene and stir for 90 minutes at 65℃ and 400 rpm to obtain a first asphalt solution and a second asphalt solution. The concentration of asphalt powder in the first asphalt solution is 250 g / L and the concentration of asphalt powder in the second asphalt solution is 370 g / L. S2.2 Spray the first asphalt solution onto the surface of the mold to form a first film with a thickness of 140μm. Then, in an inert atmosphere, heat the first film to 350℃ at a rate of 2℃ / min and keep it at that temperature for 70min to cure it, thus obtaining the bottom film. S2.3. Spray the second asphalt solution onto the surface of the base film to form a second film with a thickness of 60 μm. Then, in an inert atmosphere, heat the second film to 350°C at a rate of 2°C / min and keep it at that temperature for 45 min to cure it, thus obtaining the asphalt film. S3.1 Place the asphalt film on a graphite plate and flatten it with a breathable pressing block with a porosity > 80%. Then, in an inert atmosphere, heat it to 1000℃ at 5℃ / min and carbonize it for 4.5h to obtain a glassy carbon film. S3.2. The glassy carbon film is heated to 2900℃ at a rate of 100℃ / h, held at that temperature for 4h, and then cooled to obtain a graphite film.
[0047] It is basically the same as Example 1, except that the mass concentration of asphalt powder in the first asphalt solution in step S2.1 is lower than that in the second asphalt solution.
[0048] Comparative Example 2: S1. Phenolic resin is added to a ball mill and ball milled using grinding balls to obtain resin powder with a particle size of 35μm. The grinding balls are polyurethane-coated iron core grinding balls with a particle size of 6mm. S2.1. The resin powder is added to xylene in two batches and stirred at 65℃ and 400rpm for 90min to obtain a first asphalt solution and a second asphalt solution. The concentration of asphalt powder in the first asphalt solution is 370g / L and the concentration of asphalt powder in the second asphalt solution is 250g / L. S2.2 Spray the first asphalt solution onto the surface of the mold to form a first film with a thickness of 140μm. Then, in an inert atmosphere, heat the first film to 350℃ at a rate of 2℃ / min and keep it at that temperature for 70min to cure it, thus obtaining the bottom film. S2.3. Spray the second asphalt solution onto the surface of the base film to form a second film with a thickness of 60 μm. Then, in an inert atmosphere, heat the second film to 350°C at a rate of 2°C / min and keep it at that temperature for 45 min to cure it, thus obtaining the asphalt film. S3.1 Place the asphalt film on a graphite plate and flatten it with a breathable pressing block with a porosity > 80%. Then, in an inert atmosphere, heat it to 1000℃ at 5℃ / min and carbonize it for 4.5h to obtain a glassy carbon film. S3.2. The glassy carbon film is heated to 2900℃ at a rate of 100℃ / h, held at that temperature for 4h, and then cooled to obtain a graphite film.
[0049] It is basically the same as Example 1, except that the resin material in step S1 is not fired.
[0050] Comparative Example 3: S1.1 Phenolic resin is calcined at 450°C for 1.2 hours in an inert atmosphere to obtain an asphalt-like substance; S1.2 Add the asphalt-like substance to a ball mill and use grinding balls to ball mill it to obtain asphalt powder with a particle size of 35μm. The grinding balls are polyurethane-coated iron core grinding balls with a particle size of 6mm. S2.1. Add the asphalt powder in two batches to xylene and stir for 90 minutes at 65℃ and 400 rpm to obtain a first asphalt solution and a second asphalt solution. The concentration of asphalt powder in the first asphalt solution is 370 g / L and the concentration of asphalt powder in the second asphalt solution is 250 g / L. S2.2 Spray the first asphalt solution onto the surface of the mold to form a first film with a thickness of 60μm. Then, in an inert atmosphere, heat the first film to 350℃ at a rate of 2℃ / min and keep it at that temperature for 45min to cure it, thus obtaining the bottom film. S2.3. Spray the second asphalt solution onto the surface of the base film to form a second film with a thickness of 140μm. Then, in an inert atmosphere, heat the second film to 350℃ at a rate of 2℃ / min and keep it at that temperature for 70min to cure it, thus obtaining the asphalt film. S3.1 Place the asphalt film on a graphite plate and flatten it with a breathable pressing block with a porosity > 80%. Then, in an inert atmosphere, heat it to 1000℃ at 5℃ / min and carbonize it for 4.5h to obtain a glassy carbon film. S3.2. The glassy carbon film is heated to 2900℃ at a rate of 100℃ / h, held at that temperature for 4h, and then cooled to obtain a graphite film.
[0051] The process is basically the same as in Example 1, except that the thickness of the first film in step S2.2 is 60 μm and the thickness of the second film in step S2.3 is 140 μm.
[0052] Performance testing: Shrinkage test: The thickness of the asphalt film obtained in step S2.3 of Examples 1-4 and Comparative Examples 1-3 was measured using a measuring tool and recorded as T0. Then, the asphalt film was carbonized and graphitized according to the process in step S3 to obtain a graphite film. The thickness of the graphite film was then measured and recorded as T1. The thickness shrinkage rate was then calculated by (T0-T1) / T0×100%, and the calculation results are shown in Table 1.
[0053] Table 1. Shrinkage rate of graphite film thickness: As shown in Table 1, the thickness shrinkage rates of the graphite films prepared in Examples 1-4 were all lower than those in Comparative Examples 1-3, with Example 2 exhibiting the lowest shrinkage rate at 8.6%. The shrinkage rate of Example 1 was 12.8%, significantly lower than the 22.4% of Comparative Example 1, indicating that the gradient structure with a higher concentration of asphalt powder in the first asphalt solution than in the second asphalt solution effectively reduced the shrinkage rate of the graphite film. Example 2, based on Example 1, further added carbon nanofibers to the first asphalt solution, further reducing the shrinkage rate to 8.6%, demonstrating even better shrinkage control.
[0054] In Examples 3 and 4, the thickness ratio of the first film and the second film was adjusted, and their shrinkage rates were 14.5% and 13.7%, respectively, both higher than those in Example 1. This indicates that the change in the thickness ratio of the first film and the second film will affect the shrinkage performance of the final graphite film.
[0055] Compared with Example 1, Comparative Example 3 differs in that the thickness of the first film formed by the high-concentration asphalt solution is reduced to 60 μm, while the thickness of the second film formed by the low-concentration asphalt solution is increased to 140 μm, and its shrinkage rate is increased to 25.6%. This indicates that the thickness ratio of the high-concentration asphalt layer to the low-concentration asphalt layer needs to be controlled within a reasonable range in order to effectively reduce the shrinkage rate of the graphite film during the carbonization process.
[0056] Comparative Example 2 did not pre-fire the resin material, and the resulting graphite film had the highest shrinkage rate of 35.8%, which was significantly higher than that of Examples 1-4. This indicates that pre-firing the asphalt-like substance before preparing the graphite film can effectively reduce the thickness shrinkage during the carbonization process of the film.
[0057] Other embodiments of this disclosure will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This application is intended to cover any variations, uses, or adaptations of this disclosure that follow the general principles of this disclosure and include common knowledge or customary techniques in the art not disclosed herein. The specification and examples are to be considered exemplary only, and the true scope and spirit of this disclosure are indicated by the following claims.
Claims
1. A method for preparing a graphite thin film, characterized in that, The preparation method includes the following steps: S1. The resin material is fired in an inert atmosphere to obtain an asphalt-like substance, and then the asphalt-like substance is ball-milled to obtain asphalt powder. S2. The asphalt powder is divided into two batches and dissolved and filtered in an organic solvent to obtain a first asphalt solution and a second asphalt solution. The first asphalt solution is sprayed onto the surface of the mold and cured to obtain a bottom film. The second asphalt solution is then sprayed onto the surface of the bottom film and cured to obtain an asphalt film. The mass concentration of asphalt powder in the first asphalt solution is higher than that in the second asphalt solution. S3. Place the asphalt film on a graphite plate and flatten it with a breathable pressing block to carbonize it, thereby obtaining a glassy carbon film. Then, graphitize the glassy carbon film to obtain a graphite film.
2. The method for preparing a graphite thin film according to claim 1, characterized in that, The resin material in step S1 includes at least one of phenolic resin, furan resin, polycarbodiimide resin, and polyimide resin.
3. The method for preparing a graphite thin film according to claim 2, characterized in that, Step S1 includes: S1.1 The resin material is fired in an inert atmosphere at 370~550℃ for 0.5~2h to obtain an asphalt-like substance; S1.2 Add the asphalt-like substance to a ball mill and use grinding balls to ball mill to obtain asphalt powder with a particle size of 20~50μm. The grinding balls are polyurethane-coated iron core grinding balls with a particle size of 3~10mm.
4. The method for preparing a graphite thin film according to claim 1, characterized in that, The organic solvent in step S2 includes at least one of polyvinyl chloride, petroleum ether, methyl chloride, and xylene.
5. The method for preparing a graphite thin film according to claim 4, characterized in that, Step S2 includes: S2.
1. Add the asphalt powder in two batches to an organic solvent and stir for 60-120 minutes at 50-80℃ and 300-500 rpm to obtain a first asphalt solution and a second asphalt solution. The concentration of asphalt powder in the first asphalt solution is 320-410 g / L, and the concentration of asphalt powder in the second asphalt solution is 200-300 g / L. S2.2 Spray the first asphalt solution onto the surface of the mold to form a first film. Then, in an inert atmosphere, heat the first film to 300-400°C at a rate of 1-3°C / min and keep it at that temperature for 40-100 minutes to cure it, thus obtaining the bottom film. S2.
3. Spray the second asphalt solution onto the surface of the base film to form the second film. Then, in an inert atmosphere, heat the second film to 300-400℃ at a rate of 1-3℃ / min and keep it at that temperature for 30-60 minutes to cure it, thus obtaining the asphalt film.
6. The method for preparing a graphite thin film according to claim 5, characterized in that, Step S2.1 also includes: S2.1 Divide the asphalt powder into two batches. Add the first batch of asphalt powder and carbon nanofibers with a length of 1~5μm to an organic solvent and stir for 60~120min at 50~80℃ and 300~500rpm to obtain the first asphalt solution. Add the second batch of asphalt powder to an organic solvent and stir for 60~120min at 50~80℃ and 300~500rpm to obtain the second asphalt solution. The concentration of asphalt powder in the first asphalt solution is 320~410g / L and the concentration of carbon nanofibers is 5~15g / L. The concentration of asphalt powder in the second asphalt solution is 200~300g / L.
7. A method for preparing a graphite thin film according to claim 5 or 6, characterized in that, The total thickness of the first film and the second film is 100~300μm, and the thickness ratio of the first film to the second film is (65~75):(25~35).
8. The method for preparing a graphite thin film according to claim 1, characterized in that, In step S3, the porosity of the air-permeable block is >80%, and the weight of the air-permeable block on the asphalt film is less than 0.1 g / cm³. 2 .
9. The method for preparing a graphite thin film according to claim 8, characterized in that, Step S3 includes: S3.1 Place the asphalt film on a graphite plate and flatten it with a breathable pressing block. Then, in an inert atmosphere, heat it to 1000℃ at 2~7℃ / min for 3~6 hours to obtain a glassy carbon film. S3.
2. Heat the glassy carbon film to 2800-3000℃ at a rate of 90-110℃ / h, hold for 3-5 hours, and then cool down to obtain a graphite film.
10. A graphite film, characterized in that, The graphite film is prepared by any one of the graphite film preparation methods according to claims 1-9.